2020
DOI: 10.1055/s-0040-1722199
|View full text |Cite
|
Sign up to set email alerts
|

Tunisian Newborn's Cord Blood: Reference Values of Complete Blood Count and Hemoglobin Fractions

Abstract: Objective This study was aimed to establish local reference values for hematological indices and hemoglobin (Hb) fractions in umbilical cord blood (UCB) for the northern population of Tunisia. Study Design Our study included full-term newborns by vaginal deliveries. Hematological parameters were collected using an automated blood cell counter. The amounts of Hb fractions were measured by capillary electrophoresis of Hb. Statistical analysis was performed using R software. Results A tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Glasser et al have evaluated the lymphocyte subsets in newborns and stated that lymphocyte subgroups differed between the sexes 35 . It has been previously shown that the number of lymphocytes, neutrophils, monocytes and leukocytes is not affected by gender in term newborns 33,36,37 . In our results, it was shown that leukocyte parameters were similar in both sexes in preterm infants born before the 32 nd weeks of gestation.…”
Section: Resultsmentioning
confidence: 94%
“…Glasser et al have evaluated the lymphocyte subsets in newborns and stated that lymphocyte subgroups differed between the sexes 35 . It has been previously shown that the number of lymphocytes, neutrophils, monocytes and leukocytes is not affected by gender in term newborns 33,36,37 . In our results, it was shown that leukocyte parameters were similar in both sexes in preterm infants born before the 32 nd weeks of gestation.…”
Section: Resultsmentioning
confidence: 94%
“…In Tunisia, nationwide neonatal screening for hemoglobinopathies has not been implemented, which becomes an urgent need to set up a new national screening program hence the interest of our study. A previous study made by our laboratory aimed to establish local reference values among normal subjects for hematological indices and hemoglobin (Hb) fractions in umbilical cord blood (UCB) for the northern population of Tunisia 15 . Their data suggest reference values that could be useful for neonatal patients’ laboratory results and clinical interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies of abnormal hemoglobin in North African Countries 14 . An updated review of the epidemiologic and molecular data among Tunisian subjects was reported by Fattoum S in 2006 15 …”
mentioning
confidence: 99%